Analysis of obstetric and gynecological surgeries among adolescent girls: lessons for prevention - Kalra, Ruchi; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Health of adolescent girls is a priority. Any operative surgery affects her physical & psychological health adversely. Aim: The study was done to analyze the operative burden on adolescent girls and identify the health needs of adolescent girls at our institute. Methods: A cross sectional study was done from May 2010 till Aug 2013. All adolescent girls (19 years age and below) operated during this period at department of obstetrics & gynaecology, People’s college of medical science & RC, Bhopal were included. Results: The operations were done on 54 adolescent girls during this period which was 1.37% of the total surgeries. Age wise distribution was as 50% were of 19 years age, 37% were 18 years, 7.4% were of 17 years and 5.5% were 16 years and below. 41% of them were admitted with labour complaints, 26% cases as abortions, 13% cases with pain in abdomen. 11% of cases had cyclical pain with primary amenorrhoea 5% were admitted with Primary amenorrhoea, 4% had complaints of perineum pain. Maximum surgeries for obstetrical indications were caesarean sections (41% cases) followed by suction evacuation for abortion(26%). Among gynecological surgeries, maximum were done for imperforate hymen & partial vaginal septum (11% casesexploratory laparotomy for benign ovarian masses (9.25% cases). Diagnostic laparoscopy for primary amenorrhea was done (5.5% cases) and operative laparoscopy (3.7% cases). 1.85% cases each were of pelvic abscess and bartholin cyst where I&D and marsupialization were done respectively. Conclusions: Obstetric operative burden on adolescent girls was very high. 67% of obstetric related surgeries can be prevented by educating and encouraging them to delay the onset of sexual activity and also by providing health related and contraceptive advices in schools and community settings.